International convergence of per capita incomes during recent globalization 1990–2019 - Kowall, Nikolaus (Momentum Quarterly, 2022)
The global interpersonal income distribution illustrates the inequality between individuals in the world. Because country specifics are overlooked, a national analysis framework is a useful addition. During the recent globalization from 1990 to 2019, there was a convergence of incomes between countries and populations. Both the international and the population-weighted Gini indicate that this convergence began around the turn of the millennium. If the US GDP per capita is used as the standard, the convergence process focuses on the new EU member states as well as on South and East Asia. Most of the traditional industrialized countries fell behind in terms of GDP per capita compared to the USA. The majority of the states that recorded convergence from 1990 to 2019 recently had a more egalitarian income distribution than the USA. This suggests that the growth in GDP per capita the new EU member states and in South and East Asia was more noticeable in the middle of society than in the USA.
Keywords: Inequality; international income distribution; convergence